Robustness of Indoor Aquatic Mesocosm Experimentations and Data Reusability to Assess the Environmental Risks of Nanomaterials - Nassar, Mohammad; Auffan, Mélanie; Santaella, Catherine; Masion, Armand; Rose, Jérôme (Frontiers in Environmental Science, 2021)
Indoor aquatic mesocosms are increasingly used in nanosafety to assess the behavior, fate, and impacts of engineered nanomaterials (ENMs) in aquatic environments using relevant exposure scenarios. The robustness of 60 L freshwater mesocosm experimentation was tested on the basis of the reusability of the data collected in a database named MESOCOSM regarding mesocosm experiments examining the environmental risks of CeO2 ENMs. We observed high reliability of the measured variables across replicates. The sensitivity of this mesocosm methodology was evidenced by the contrasted ecosystem responses revealed by a multivariate analysis. We also observed that adding variables to the data set up to 15% did not affect the outcome of the analysis of the results. This ability to buffer this variability demonstrates that the indoor aquatic mesocosms are robust tools contributing to the environmental risk assessment of ENMs, and stresses the benefit of reusing the data stored in databases such as MESOCOSM adhering to the findable, accessible, interoperable, reusable (FAIR) data principles.